Examining The Effect Of Leadership Style And Organizational Culture On Nurses’ Performance Through Work Motivation In A Regional Public Hospital - Ariefah Maulani; Uli Wildan Nuryanto; Khaeruman Khaeruman (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The purpose of this research is to examine the influence of leadership style and organizational culture on nurses’ performance, with work motivation serving as a mediating variable. The study not only focuses on the direct relationships among the variables but also investigates how work motivation mediates the link between leadership, organizational culture, and performance. This research applies a quantitative method with a survey approach. Primary data were collected through questionnaires distributed to 175 nurses working at RSUD Kota Cilegon. The data were then analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) to test the relationships among the research variables simultaneously. The findings reveal that leadership style and organizational culture have a positive and significant impact on nurses’ performance. In addition, work motivation is proven to function as a mediating variable that strengthens this relationship, thereby enhancing the influence of both leadership and organizational culture on nurses’ performance.